2018
DOI: 10.1121/1.5040489
|View full text |Cite
|
Sign up to set email alerts
|

Binaural rendering of Ambisonic signals by head-related impulse response time alignment and a diffuseness constraint

Abstract: Binaural rendering of Ambisonic signals is of great interest in the fields of virtual reality, immersive media, and virtual acoustics. Typically, the spatial order of head-related impulse responses (HRIRs) is considerably higher than the order of the Ambisonic signals. The resulting order reduction of the HRIRs has a detrimental effect on the binaurally rendered signals, and perceptual evaluations indicate limited externalization, localization accuracy, and altered timbre. In this contribution, a binaural rend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 30 publications
1
75
1
3
Order By: Relevance
“…Future work will look at adapting the AIO algorithm to implement frequency-dependent gains for each loudspeaker instead of a single gain as is the current case. Planned subsequent work will also look at integrating the presented AIO method with other pre-processing techniques for improving high-frequency reproduction of binaural Ambisonic rendering using virtual loudspeakers, such as diffuse-field equalization [59], direction-bias equalization [58] and time-alignment [25][26][27]. Preliminary tests have shown that combining AIO with these equalization methods can produce even greater improvements to high-frequency reproduction, and possibly allow for the perceptual experience of a higher Ambisonic order without an increase in convolutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future work will look at adapting the AIO algorithm to implement frequency-dependent gains for each loudspeaker instead of a single gain as is the current case. Planned subsequent work will also look at integrating the presented AIO method with other pre-processing techniques for improving high-frequency reproduction of binaural Ambisonic rendering using virtual loudspeakers, such as diffuse-field equalization [59], direction-bias equalization [58] and time-alignment [25][26][27]. Preliminary tests have shown that combining AIO with these equalization methods can produce even greater improvements to high-frequency reproduction, and possibly allow for the perceptual experience of a higher Ambisonic order without an increase in convolutions.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent methods for binaural Ambisonic rendering have moved away from the virtual loudspeaker approach and instead focused on order truncation of an approximately spatially continuous spherical harmonic (SH) represented HRIR dataset [21,22]. However, this causes severe high-frequency roll-off at low truncation orders, which requires compensation through pre-processing techniques [23] such as equalization [24], time-alignment [25][26][27] and more recently magnitude least squares [28]. As this also requires a highly dense dataset of HRIRs measured at points on the sphere distributed by a regular (or at least semi-regular) quadrature such as the Lebedev grid [29], it is, therefore, considered infeasible for individualization at present, despite techniques such as reciprocity [30] and multiple swept sine [31] offering faster measurement times.…”
Section: Introductionmentioning
confidence: 99%
“…For decoding to headphones, it should be considered to either take only as few HRIR directions to decode to as possible [7,8], before signals get convolved and mixed to avoid coloration at frontal directions where delays in the HRIRs change too strongly over the direction to get resolved properly [9,10]. Alternatively, the approach in [11] proposed removal of the HRIR delay at high frequencies and diffuse-field covariance equalization by a 2 × 2 filter system, cf. Sect.…”
Section: Fig 51 Block Diagram As Inmentioning
confidence: 99%
“…Spatial encoding of simulation output is a necessary step towards full virtual acoustic auralisation. A good candidate is the Ambisonics framework [11], [12], which can be decoded to arbitrary playback systems [13], [14]. For wave-based volumetric methods, previous approaches have followed from those used in spatial recording.…”
Section: Introductionmentioning
confidence: 99%